Navigating restricted social rights: networked individualism as a coping mechanism for undocumented Chinese immigrants in the United States - Lin, Shasha; Zheng, Jin; Zhou, Min (Ethnic and racial studies, 2025)
This paper explores how networked individualism was, as opposed to traditional migrant networks, utilized by post-COVID-19 undocumented Chinese immigrants to cope with restricted social rights and socioeconomic constraints upon arrival in the United States. Drawing on in-depth interviews and participant observation in a Chinese ethnoburb in the San Gabriel Valley, Los Angeles, we found that these immigrants had few connections to established migrant networks and diasporic Chinese communities, but managed to exercise individual agency to leverage online platforms to crowdsource information and resources conducive to migrant adaptation. However, while it helped ease precarity in housing, employment, and legal status, networked individualism reinforced undocumented immigrants’ disengagement from both their ethnic community and the larger society, which exacerbated their double marginalization and posed challenges to their social mobility. Our paper contributes to migration scholarship by theorizing how social networks evolve in the era of digital globalization to shape migrant adaptation.